A bimodal neurophysiological study of motor control in attention-deficit hyperactivity disorder: a step towards core mechanisms? - Heinrich, Hartmut; Hoegl, Thomas; Moll, Gunther; Kratz, Oliver (Brain, 2014)
Knowledge about the core neural mechanisms of attention-deficit hyperactivity disorder, a pathophysiologically heterogeneous psychiatric disorder starting in childhood, is still limited. Progress may be achieved by combining different methods and levels of investigation. In the present study, we investigated neural mechanisms of motor control in 19 children with attention-deficit hyperactivity disorder (aged 9-14 years) and 21 age-matched typically developing children by relating neural markers of attention and response control (using event-related potentials) and measures of motor excitability/inhibition (evoked by transcranial magnetic stimulation). Thus, an interplay of processes at a subsecond scale could be studied. Using a monetary incentives-based cued Go/No-Go task, parameters that are well-known to be reduced in attention-deficit hyperactivity disorder were analysed: event-related potential components P3 (following cue stimuli; in Go and No-Go trials) and contingent negative variation as well as the transcranial magnetic stimulation-based short-interval intracortical inhibition measured at different latencies in Go and No-Go trials. For patient and control groups, different associations were obtained between performance, event-related potential and transcranial magnetic stimulation measures. In children with attention-deficit hyperactivity disorder, the P3 amplitude in Go trials was not correlated with reaction time measures but with short-interval intracortical inhibition at rest (r=0.56, P=0.01). In No-Go trials, P3 and short-interval intracortical inhibition after inhibiting the response (at 500 ms post-stimulus) were correlated in these children only (r=0.62; P=0.008). A classification rate of 90% was achieved when using short-interval intracortical inhibition (measured shortly before the occurrence of a Go or No-Go stimulus) and the amplitude of the P3 in cue trials as input features in a linear discriminant analysis. Findings indicate deviant neural implementation of motor control in children with attention-deficit hyperactivity disorder reflecting compensatory cognitive mechanisms as a result of a basal motor cortical inhibitory deficit (reduced activation of inhibitory intracortical interneurons). Both deviant inhibitory and attentional processes, which are not related to each other, seem to be characteristic for attention-deficit hyperactivity disorder at the neural level in motor control tasks. The underlying neural mechanisms, which are probably not restricted to the motor cortex and the posterior attention network, may play a key role in the pathophysiology of this child psychiatric disorder. The high classification rate can further be interpreted as a step towards the development of neural markers. In summary, the bimodal neurophysiological concept may contribute to developing an integrative framework for attention-deficit hyperactivity disorder.
EVALuna2:23881